(3GdQSGdI GdehSheI HGdJYfja hGdJgLjfs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3JhcdJ Ydi GdMGce Gdehdi GdEdg GdYGde GdCYdi CeG HYO aGdLdGd hGdYRI hGdMeO hGdJbOjS hGdbOQI hGdeLO ddehdi GdEdg GdMGce s
(3BNQgG (B:s
(3aeG Ydi GdQShd EdG GdHdGZ GdeHjf hGdfUjMI def CHUQ dfaSg ef Gdehbfjf HYO GdJhcd Ydi hdi GdMb JeJ GdQSGdI hGdMeO ddMGce Gdehdi hdi GdfYeI hGdTcQ dhdjg GdgGOi EeGe GdCFeI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B51s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ , RNGQa s
Keywords: (3abg GdePGgH GdCNQis